Vampire Prince - Shan, Darren (New York Little, Brown, 2004)
Betrayed by Kurda Smahlt and reeling from the brutal slaying of Gavner Purl, the vampire's assistant, Darren Shan, finds himself branded a traitor and hunted by the vampire clan.
Sequel to: Trials of death.
"First published in Great Britain by Collins in 2002"--T.p. verso.
890L
96840
Keywords: Vampires; Horror stories